Phase controlled synthesis of CuSbS2 nanostructures: Effect of reaction conditions on phase purity and morphology. (15th December 2017) - Pal, Mou; Torres Luna, Y.; Silva González, R.; Mathews, N.R.; Paraguay-Delgado, F.; Pal, U.
Abstract: Development of photovoltaic materials made of earth-abundant nontoxic elements is one of the primary goals of current energy research to meet the increasing demand of electrical energy worldwide. In this context, CuSbS2 is proposed as an alternative absorber material for thin film solar cells due to its appropriate optical band gap, high absorption coefficient, and attractive power conversion efficiency (23%, theoretical). Here we report a surfactant-free solvothermal method using a mixed solvent constituting ethylenediamine (En) and deionized water for the synthesis of CuSbS2 nanocrystals of different morphologies. The nature of solvent, reaction time and temperature of solvothermal treatment were found to have significant impacts on the shape and structural phase of CuSbS2 nanostructures. Structural, optical and morphological properties of the nanostructures were thoroughly characterized using different techniques such as X-ray diffraction, Raman scattering, scanning electron microscopy, transmission electron microscopy, energy dispersive spectroscopy, X-ray photoelectron spectroscopy, and UV–Vis absorption spectroscopy. Effect of solvothermal conditions on the formation of stoichiometric, phase pure CuSbS2 have been discussed. Graphical abstract: Highlights: Phase pure CuSbS2 nanocrystals were syntheiszed by solvothermal method. Ethylenediamine (En), water and En-water mixture were used as reaction media. Use of binary solvent improves the crystallinity and changes drastically the shape and size of the CuSbS2 nanostructures. The optical behavior and high yield of the product suggests the suitability of this material as solar absorber.